Evaluation of the Clinical, Child, and Parental Satisfaction with Zirconia Crowns in Maxillary Primary Incisors: A Systematic Review - Mohammad Hassan Hamrah; Saeedeh Mokhtari; Zahra Hosseini; Maryam Khosrozadeh; Sepideh Hosseini; Elaha Somaya Ghafary; Mohammad Hussain Hamrah; Narges tavana (International Journal of Dentistry)
Background. With the increasing demand for aesthetics in children and their parents, the treatment of decayed primary anterior teeth is one of the biggest challenges in pediatric dentistry. Zirconia crowns have provided a treatment alternative to address the aesthetic concerns and ease of placement of extracoronal restorations on primary anterior teeth. Methods. The electronic databases including PubMed, Scopus, Google Scholar, and Embase were searched on articles published between January 2010 and January 2021. Studies relating to evaluating the clinical success and satisfaction of both parents and children about zirconia crowns in maxillary primary incisors were reviewed. Results. Nine studies met the criteria for final inclusion. Findings from these studies showed that parental and child satisfaction with zirconia crowns is high with clinically acceptable restorations in the maxillary primary incisors. Conclusion. Parental and child satisfaction with zirconia crowns is high with clinically acceptable restorations in the maxillary primary incisors. In addition, larger sample sizes and longer follow-ups are required in future studies.